The Salmonella phage shock protein system is required for defense against host antimicrobial peptides - Massicotte, Marie-Ange; Fiebig, Aline A.; Bogza, Andrei; Coombes, Brian K. (PLOS Pathogens, 2025)
Author summary Salmonella enterica is an important global pathogen that infects a wide range of mammalian hosts, requiring it to survive in diverse and hostile environments. A key aspect of Salmonella pathogenesis is its ability to reside within host immune cells like macrophages, where it must rapidly adapt to intracellular conditions. To do so, the bacteria must ensure correct spatiotemporal expression of virulence genes to maximise fitness in each environment. To better understand how Salmonella modulates its gene expression during infection of host cells, we defined its transcriptome at four distinct stages of primary murine macrophage infection. Our findings reveal that the first stage of early infection is dominated by changes in gene expression of metabolic circuits. Furthermore, we identified the phage-shock protein (Psp) system as highly expressed within intracellular Salmonella throughout the course of infection as a result of regulatory evolution that coordinates its expression with virulence genes. We showed that this system is required for bacterial survival within macrophages and host tissues by mediating resistance to host cationic antimicrobial peptides. These findings highlight the dynamic nature of Salmonella’s transcriptional response during macrophage infection and uncover a previously unknown function of the Psp system as an adaptive mechanism for evading host immune defenses.